A systematic review and synthesis of outcome domains for use within forensic services for people with intellectual disabilities. Issue 1 (January 2017) - Morrissey, Catrin; Langdon, Peter E.; Geach, Nicole; Chester, Verity; Ferriter, Michael; Lindsay, William R.; McCarthy, Jane; Devapriam, John; Walker, Dawn-Marie; Duggan, Conor; Alexander, Regi
Abstract : Background: There is limited empirical information on service-level outcome domains and indicators for the large number of people with intellectual disabilities being treated in forensic psychiatric hospitals. Aims: This study identified and developed the domains that should be used to measure treatment outcomes for this population. Method: A systematic review of the literature highlighted 60 studies which met eligibility criteria; they were synthesised using content analysis. The findings were refined within a consultation and consensus exercises with carers, patients and experts. Results: The final framework encompassed three a priori superordinate domains: (a) effectiveness, (b) patient safety and (c) patient and carer experience. Within each of these, further sub-domains emerged from our systematic review and consultation exercises. These included severity of clinical symptoms, offending behaviours, reactive and restrictive interventions, quality of life and patient satisfaction. Conclusions: To index recovery, services need to measure treatment outcomes using this framework.